Plasma metabolome of children with aberrant cholesterol and modulation by navy bean and rice bran consumption - Li, Katherine Jia, author; Ryan, Elizabeth, advisor; Prenni, Jessica, committee member; Clark, Maggie, committee member (Colorado State University. Libraries, 2018)
Abnormal cholesterol in childhood predicts cardiovascular disease (CVD) risk in adulthood. Navy beans and rice bran have demonstrated efficacy in regulating blood lipids in adults and children; however, their effects on modulating the child plasma metabolome has not been investigated and warrants investigation. A pilot, randomized-controlled, clinical trial was conducted in 38 children (10 ± 0.8 years old) with abnormal cholesterol. Participants consumed a snack for 4 weeks containing either: no navy bean or rice bran (control); 17.5 g/day cooked navy bean powder; 15 g/day heat-stabilized rice bran, or; 9 g/day navy beans and 8 g/day rice bran. Plasma metabolites were extracted using 80% methanol for global, non-targeted metabolic profiling via ultra-high performance liquid-chromatography tandem mass spectrometry. To examine correlations between baseline serum lipid levels and plasma metabolites, non-parametric Spearman's correlation coefficients (rs) were computed between serum total cholesterol, low-density lipoprotein (LDL) cholesterol, high-density lipoprotein (HDL) cholesterol, and triglycerides (TG) with 805 plasma metabolites. Differences in plasma metabolite levels after 4 weeks of dietary intervention compared to control and baseline were analyzed using analysis of variance and Welch's t-tests (p≤0.05). Approximately 29% of the plasma metabolome (235 metabolites) were significantly correlated with serum lipids. Plasma cholesterol was positively correlated with serum total cholesterol, and 27 plasma metabolites were found to be strongly correlated with serum TG (rs ≥0.60; p≤0.0001). Navy bean and/or rice bran consumption influenced 71 plasma compounds compared to control (p≤0.05), with lipids representing 46% of the total plasma metabolome. Significant changes were determined for 18 plasma lipids in the navy bean group and 10 plasma lipids for the rice bran group compared to control, and 48 lipids in the navy bean group and 40 in the rice bran group compared to baseline. This supports the hypothesis that consumption of these foods impact blood lipid metabolism with implications for reducing CVD risk in children. Complementary and distinct lipid pathways were affected by the diet groups, including acylcarnitines and lysolipids (navy bean), sphingolipids (rice bran), and phospholipids (navy bean + rice bran). Navy bean consumption decreased free fatty acids associated with metabolic diseases (palmitate and arachidonate) and increased the relative abundance of endogenous anti-inflammatory lipids (endocannabinoids, N-linoleoylglycine, 12,13-diHOME). Several diet-derived amino acids, phytochemicals, and cofactors/vitamins with cardioprotective properties were increased compared to control and/or baseline, including 6-oxopiperidine-2-carboxylate (1.87-fold), N-methylpipecolate (1.89-fold), trigonelline (4.44- to 7.75-fold), S-methylcysteine (2.12-fold) (navy bean), salicylate (2.74-fold), and pyridoxal (3.35- to 3.96-fold) (rice bran). Findings from this pilot study support the need for investigating the effects of these foods for longer durations to reduce CVD risk.